EFEKTIFITAS PELATIHAN PERAWATAN LUKA TINGKAT DASAR DI BAPELKES BATAM DALAM MENINGKATKAN KEMAMPUANTENAGA KEPERAWATAN DI PROVINSI KEPULAUAN RIAU - Hayati, Wilda; Suwandana, Endan (Universitas Tribhuwana Tunggadewi, 2019)
The improvement of wound care capabilityof nurses needs to be continually conducted due to the development in science and technology of the wound care. One way to improve the capabilityof the nurse can be achievedby conducting a training program. This paper is aimed to assess the effectiveness of the basic level wound care training program at Health Training Center (Bapelkes) of Batam in the improvement of the nurses’ capabilities in the Kepulauan Riau Province. Thisstudy implements qualitative descriptive method by using questionnaires as research instrument which were distributed to three groups of respondents, i.e. the alumni, the alumni’s mentors, and the alumni’s working partners,out of three training batches between 2011-2013. The variables evaluated in this study include performance, working motivation, professional competency, and training competency. Descriptive statistical analysis methods and analytic statistics (simple linear regression) are also used in data analysis. The results of the study show that the training program is effective in improving the nurses’ capability in all evaluated variables with the average improvement percentage of 96,88% (based on response of the alumni), 90,63% (based on the response of the alumni’s mentors), and 92,19% (based on the response of the alumni’s working partners). The study also concludes that the correlation of responsesamong the group of respondents showing that the correlation of the responses between the alumni and the alumni’s mentors is strongly significant with the coefficient correlation (R2) of 0.804 and strong with the R2 of 0,516 for the correlation of the responses between the alumni and the alumni’s working partners. This means that the assessment given by training alumni, alumni superiors and alumni colleagues is not biased and the three groups of respondents suppot each other/ have in common, assessments given by training alumni and above alumni have a very strong relationship with the correlation coefficient (R2) 0.804. Keywords : Post-training evaluation; wound care; nurse.